1997
DOI: 10.1029/97jd00459
|View full text |Cite
|
Sign up to set email alerts
|

A globally balanced two‐dimensional middle atmosphere model: Dynamical studies of mesopause meridional circulation and stratosphere‐mesosphere exchange

Abstract: In addition, the model shows that the most active region for the stratosphere-mesosphere mass exchange is at the summer polar stratopause. The active exchange is driven by a strong summer mesospheric drag force through the "downward control" principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The effects of tides are not included in this run, and the ozone concentrations only show small dependence on the local time. The modeled ozone near local noon is consistent with the measurements [Zhu et al, 1999a]. Since it is near the Northern Hemisphere summer solstice, the daytime local time duration at 40°N is about twice that at 40°S.…”
Section: Model Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The effects of tides are not included in this run, and the ozone concentrations only show small dependence on the local time. The modeled ozone near local noon is consistent with the measurements [Zhu et al, 1999a]. Since it is near the Northern Hemisphere summer solstice, the daytime local time duration at 40°N is about twice that at 40°S.…”
Section: Model Resultssupporting
confidence: 82%
“…On the other hand, for airglow originating from metastable electronic transitions, such as O 2 (a 1 D g ! X 1 S g ), which produces the 1.27-mm airglow emission, the spontaneous relaxation times at high altitudes are usually longer than the photochemical times of the relevant chemical species and could be comparable to the diurnal variation and transport timescale, leading to a strong coupling between the photochemistry forced by the diurnally varying photolysis rates, the advective transport by the tidal velocities, and the diurnal variation in rate coefficients induced by the tidal temperature perturbations in the mesosphere and lower thermosphere [Zhu et al, 1999a[Zhu et al, , 2000].…”
Section: Introductionmentioning
confidence: 99%
“…The model proposed by Zhu et al (1997) is consistent with meridional velocities of 20-30 m/s measured by the Upper Atmosphere Research Satellite (UARS), and supports a mesosphere forced by breaking/dissipating gravity waves. However, a fine-tuning of the parameterization schemes is still an important subject for the modeling community (e.g., Hoffmann et al, 2010).…”
Section: Introductionsupporting
confidence: 52%
“…The MRC has mean absolute magnitude of 5-25 m/s during solstices, which follows from climatologies obtained from satellite measurements (McLandress et al, 1996). Also, the Zhu et al (1997) model showed MRC magnitudes of $25 m/s around 92 km, with maximum in the summer mesopause.…”
Section: Introductionmentioning
confidence: 96%
“…This exercise provides an important cross validation between ground-and satellitebased mean wind estimates and updates earlier residual meridional wind estimates that are based upon simpler radiative heating algorithms and CIRA-86 climatological inputs [Huang and Smith, 1991 ]. Our study also provides some validation of more recent two-dimensional models of the residual mean circulation incorporating revised radiative heating and gravity wave drag parameterizations [Portmann, 1994;Zhu et al, 1997]. Section 2 describes wind and temperature observations and the model used to calculate the diabatic circulation.…”
Section: Lieberman Et Almentioning
confidence: 99%